Analysis of the Influence of Gross Regional Domestic Product Per Capita, Inflation, and Human Development Index on Regency/City Income Inequality in West Nusa Tenggara Province in 2018-2023 - Alda Gusma Futri; Muhammad Alwi; Ida Ayu Suprapti (International Journal of Economics Studies, 2026)
This study aims to analyze the influence of Gross Regional Domestic Product Per Capita, Inflation, and Human Development Index on Regency/City Income Inequality in West Nusa Tenggara Province during 2018-2023. This research is a quantitative research with a descriptive analysis method. The data used is in the form of crosssections of 10 regencies/cities in West Nusa Tenggara Province and time series during 2018-2023. The data was processed by panel analysis using Common Effect Model regression through the Evies 12 program. The results of this study are that partially the variables of Gross Regional Domestic Product Per Capita have a negative and insignificant effect on income inequality, the inflation variable has a positive and insignificant effect on income inequality, and the Human Development Index variable has a positive and significant effect on income inequality. Meanwhile, simultaneously the research variables have an effect on income inequality. In this study, only 29.49% of income inequality was influenced by the variables of Gross Regional Domestic Product Per Capita, Inflation, and the Human Development Index, while the remaining 70.51% was influenced by other variables outside the model that were not used in the study. Based on the results of the study, it is influenced by economic growth and the improvement of the quality of human development which is not in line with income equity. Therefore, an inclusive economic policy is needed that focuses on equitable access to economic resources and opportunities, especially for low-income groups and disadvantaged areas. In addition, the government must ensure that the benefits of increasing HDI must be felt equally by all people in every district/city in West Nusa Tenggara Province so as not to widen income inequality.